Bacterial endosymbiont Cardinium cSfur genome sequence provides insights for understanding the symbiotic relationship in Sogatella furcifera host - Zeng, Zhen; Fu, Yating; Guo, Dongyang; Wu, Yuxuan; Ajayi, Olugbenga Emmanuel; Wu, Qingfa (BIOMED, 2018)
Background: Sogatella furcifera is a migratory pest that damages rice plants and causes severe economic losses. Due to its ability to annually migrate long distances, S.furcifera has emerged as a major pest of rice in several Asian countries. Symbiotic relationships of inherited bacteria with terrestrial arthropods have significant implications. The genus Cardinium is present in many types of arthropods, where it influences some host characteristics. We present a report of a newly # identified strain of the bacterial endosymbiont Cardinium cSfur in S. furcifera.